Effectiveness of LKPD Based on Chemical Representation Using the Discovery Learning Model in Improving Science Process Skills On Chemical Equilibrium Material - Rosilawati, Ila; Riyanti, Marsella Dwi; Kadaritna, Nina (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
Abstract: Effectiveness of LKPD Based on Chemical Representation Using the Discovery Learning Model in Improving Science Process Skills in Chemical Equilibrium Material . This research aims to describe the effectiveness of chemical representation-based LKPD with discovery learning models in improving KPS in chemical equilibrium material. The population in this research is all students in class XI Science at SMAN 14 Bandarlampung for the 2022/2023 academic year. The sample was selected using purposive sampling technique. The sample in this research was class XI IPA 6 as the experimental class and XI IPA 5 as the control class. The design in this research is The Matching-Only Pretests-Posttest Control Group Design . The data analysis technique used is the difference test between two means with the Independent Samples t-Test. The research results show that the average KPS n-gain is in the high category in the experimental class and medium in the control class. The results of data analysis showed that there was a significant difference in the average KPS n-gain between the experimental class which applied LKPD based on chemical representation with the discovery learning model and the control class which used LKPD which was not based on chemical representation with the discovery learning model . Based on the research results, it can be concluded that the LKPD based on chemical representation with the discovery learning model is effective in increasing students' KPS in chemical equilibrium material.Keywords: LKPD based on chemical representation, discovery learning model, chemical equilibrium, science process skillsDOI: 10.23960/jppk.v13.i1.2024.12